Medial Sural Artery Islanded Pedicled Perforator Flap for Resurfacing Areas in the Popliteal Fossa Following Postburn Contracture Release Using Normal versus Scar Tissue - Sanjay Kumar Giri; Santanu Suba; Ahana Bandyopadhyay; R. K. Sahu; Aparna Kanungo; Reena Minz (Indian Journal of Plastic Surgery, 2024)
Background The medial sural artery perforator (MSAP) flap is reliable in resurfacing defects of the popliteal fossa. There is possibility of resurfacing the popliteal fossa defects after postburn contracture release with scarred MSAP flaps with good overall long-term outcomes.